Gender rules in the community corrections context: Examining how case managers navigate trans client supervision in a binary setting - Ellis, Taylor (Probation journal, 2024)
This article explores one US residential community corrections facility and the ways that case managers navigate working with transgender women under supervision in a facility that relies on the sex binary for housing placement. Similar to other research on this population in prisons that has been conducted both within and outside of the US context, we find that case managers contend with significant uncertainty in their work with these clients because of a lack of specific and formal training. To contend with that uncertainty, case managers reported relying on Gender Responsive Training and the Prison Rape Elimination Act to guide their understanding of and work with trans clients. However, we also found a great deal of discretion in the ways case managers managed programming for their trans clients that disrupted the gendered organization of the facility. We conclude with specific programmatic recommendations based on these findings.